2016
DOI: 10.1159/000453216
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Improves Cognitive Impairment by Regulating Apoptosis and Synaptic Plasticity in Streptozotocin-Induced Diabetic Rats

Abstract: Aims: To investigate the effects of resveratrol on cognitive impairment in streptozotocin (STZ)-induced diabetic rats and to explore the mechanisms of that phenomenon. Methods: Sixty healthy male Sprague Dawley rats were randomly divided into four groups: normal control group (Con group, n = 15), Res group (normal Sprague Dawley rats treated with resveratrol, n = 15), diabetes mellitus group (DM group, n = 15) and DM + Res group (diabetic rats treat with resveratrol, n = 15). Streptozotocin (STZ) was injected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(33 citation statements)
references
References 25 publications
5
28
0
Order By: Relevance
“…The present study provided evidence that resveratrol protects against diabetic cardiomyopathy by activating AMPK and JNK1 pathway to modulate the switch between autophagy and apoptotic machinery. Our results are supported by previous studies that autophagy is suppressed in type 2 diabetes and resveratrol acts as an regulator of autophagy [8, 13] and apoptosis [26]. …”
Section: Discussionsupporting
confidence: 92%
“…The present study provided evidence that resveratrol protects against diabetic cardiomyopathy by activating AMPK and JNK1 pathway to modulate the switch between autophagy and apoptotic machinery. Our results are supported by previous studies that autophagy is suppressed in type 2 diabetes and resveratrol acts as an regulator of autophagy [8, 13] and apoptosis [26]. …”
Section: Discussionsupporting
confidence: 92%
“…A recent study asserted that DM and subarachnoid hemorrhage could occur as a result of the apoptosis of hippocampal neurons, accompanied by increased expressions of caspase‐3, Bax, and Bcl‐2 (He, Sun, & Huang, ). Another study also has found that resveratrol has protective effect on STZ‐induced DM, which may result from inhibiting hippocampal neuron apoptosis via the Bcl‐2, Bax, and caspase‐3 signaling pathways (Z. Tian et al, ). Furthermore, lncRNAs are closely associated with some cellular stress responses such as OS, nutritional deficiency, and DNA damage (Zeng et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Of these, the fact that phosphorylation levels of SIRT1 and AMPK in Pb-exposed mice were restored by resveratrol treatment reflected the action of resveratrol on SIRT1/AMPK activation. Moreover, it is reported that resveratrol can promote SIRT1/AMPK activation (Valenti et al, 2016) and is implicated in neural plasticity (Torres-Pérez et al, 2015; Dias et al, 2016; Tian et al, 2016). Similar to our results for pSIRT1, the present study showed probe time in target area of the MWM test was also positively correlated with the ratio of pAMPK/AMPK which enhanced the link between cognition and resveratrol involving AMPK.…”
Section: Discussionmentioning
confidence: 99%